Hillforts: The Traditions of “Mottes” in the Territory of the Volyn Land in the Lithuanian Period - Panishko, Sergey (Archaeologia Lituana, 2018)
[full article, abstract in English; abstract in Lithuanian] A group of monuments, specific by their external morphological features, stands out among the late medieval fortifications on the territory of the Volyn land. The abovementioned fortifications have the form of hills (“mottes”) with the upper sites of different sizes. The tradition of constructing such hillforts spread on the territory of Volhynia from the European side. Those hillforts were the first chivalrous castles. Judging by the current level of knowledge about these fortifications on the territory of Volhynia, several groups can be distinguished. Polissia fortifications (Kamin-Kashyrsky, Lyuboml, Vetly), which are the remains of small cities, volost-sotnia centers of the 14th century, are clearly distinguished. The second group includes the fortifications represented by the medium-sized hills in Korshiv and Gorodyshche I, which, apparently, were the castles of the outstanding feudal lords. The third group is represented by the classic examples of the European complexes of “mottes and baileys” in Ratno, Falemychi, Pyatydni, Khotyn, which, apparently, were the courtyards of knights. A peculiar position is occupied by an artificial mound in the middle of the lake (crannog) in Kachyn village. Such fortifications functioning on the territory of Volhynia can be referred to the second half of the 13th to the 16thcenturies. During their existence, the social functions of these constructions could have changed.